Non-invasive assessment of phosphate metabolism and oxidative capacity in working skeletal muscle in healthy young Chinese volunteers using 31P Magnetic Resonance Spectroscopy - Li,Ming; Chen,Fei; Wang,Huiting; Wu,Wenbo; Zhang,Xin; Tian,Chuanshuai; Yu,Haiping; Liu,Renyuan; Zhu,Bin; Zhang,Bing; Dai,Zhenyu (PeerJ, 2016)
Background. Generally, males display greater strength and muscle capacity than females while performing a task. Muscle biopsy is regarded as the reference method of evaluating muscle functions; however, it is invasive and has sampling errors, and is not practical for longitudinal studies and dynamic measurement during excise. In this study, we built an in-house force control and gauge system for quantitatively applying force to quadriceps while the subjects underwent 31P Magnetic Resonance Spectroscopy (31P-MRS); our aim was to investigate if there is a sex difference of phosphate metabolite change in working muscles in young heathy Chinese volunteers. Methods. Volunteers performed knee-extending excises using a force control and gauge system while lying prone in a Philips 3T Magnetic Resonance (MR) scanner. The 31P-MRS coil was firmly placed under the middle of the quadriceps . 31P-MRS measurements of inorganic phosphate (Pi), phosphocreatine (PCr) and adenosine triphosphate (ATP) were acquired from quadriceps while subjects were in a state of pre-, during- and post-exercise. The PCr, Pi, PCr/Pi, PCr/ATP, pH, work/energy cost ratio (WE), kPCr and oxidative capacity were compared between males and females. Results. A total of 17 volunteers underwent the study. Males: N = 10, age = 23.30 ± 1.25years; females: N = 7, age = 23.57 ± 0.79 years. In this study, males had significantly greater WE (16.33 ± 6.46 vs. 7.82 ± 2.16, p = 0.002) than females. Among PCr, Pi, PCr/Pi, PCr/ATP, pH, kPCr and oxidative capacity at different exercise status, only PCr/Pi (during-exercise, males = 5.630 ± 1.647, females = 4.014 ± 1.298, p = 0.047), PCr/ATP (during-exercise, males =1.273 ± 0.219, females = 1.523 ± 0.167, p = 0.025), and ATP (post-exercise, males = 24.469 ± 3.911 mmol/kg, females = 18.353 ± 4.818 mmol/kg, p = 0.035) had significant sex differences. Males had significantly greater PCr/Pi, but less PCr/ATP than females during exercise, suggesting males had higher energy transfer efficiency than females. At the post-exercise status, the recovery of PCr did not show sex difference. Conclusions. Our in-house force control and gauge system quantitatively applied force during the exercise for 31P-MRS experiments, and a sex difference of higher energy transfer efficiency and WE was detected in males with mild loaded exercising quadriceps. This noninvasive technology allows us to further study and understand the sex difference of high energy phosphate metabolism in the future.
Keywords: 31P magnetic resonance spectroscopy; Phosphate metabolism; Oxidative capacity